Supply chain management and organizational performance: the resonant influence - Duong, Binh An Thi (2019)
Purpose A single supply chain management (SCM) practice will have a certain impact on organizational performance (OP). However, since it is placed in a system that many other practices are conducted simultaneously, the practice itself will interact with other ones (i.e. affect/be affected). As a consequence, the efficiency of the affected practice is increased and it is expected to maximize the impact of SCM practices on OP. This mechanism is named the "resonant" influence that is a new approach in the SCM literature. The purpose of this paper is to test the above mechanism toward an insight into the relationship between SCM and OP. Design/methodology/approach Two models were compared: the competitive models only exist in direct effects; and the other contains relationships between practices that are able to show the mechanism of the resonant influence, i.e. the hypothetical model. A data set gained from Vietnamese garment enterprises was used to validate the mechanism of the resonant influence. Findings Empirical evidence from Vietnamese garment sector showed that the competitive models could explain 42.8, 26.3 and 34 percent variance of operational performance, customer satisfaction and financial performance, respectively. In the meantime, the hypothetical model containing the resonant influence is capable to explain 69.5, 33.1 and 57.3 percent. For the impact of each SCM practice on OP, all relationships in the hypothetical model are also greater than those in competitive ones. These results supported the mechanism of the resonant influence. Research limitations/implications - This research provides an insight into the relationship between SCM practices and OP. By the resonant influence, the effectiveness of each affected SCM practice itself is magnified and OP is also increased remarkably. Practical implications - Understanding the resonant influence, companies can apply this mechanism to enhance effectiveness of SCM practices at the lowest cost. To this end, the SCM practices should be implemented simultaneo